Challenges and Successes in Health Communication Messaging With Asian Americans. Issue 1 (November 2022) - Caboral-Stevens, Meriam; Rainville, Alice Jo; Ford, Olivia; Yang, Xining; Donnelly, Jessica; Bessire, Rachel; Jackson-Dyer, Tameka; Sonnega, John; Wu, Tsu-Yin
Asians are the fastest growing racial and ethnic group in the United States, and in Michigan, Asians represent 3.4% of the state's population. Asians have long been aggregated as a homogeneous group and stereotyped as a "model minority." Asians, however, are very diverse, and each subgroup has different values, histories, beliefs, and dialects. The diversity among populations and variations in chronic disease risks demonstrate the importance of disaggregating Asian American ethnicities with respect to health promotion, which must be culturally and linguistically tailored to make the biggest impact. This article describes our challenges and successes in health communication messaging with Asian Americans during the 4 years of our Racial and Ethnic Approaches to Community Health (REACH) Cooperative Agreement.